Edible and Medicinal Mushrooms: Technology and Applications - Zied, Diego Cunha [UNESP]; Pardo-Giménez, Arturo (Wiley, 2017)
Comprehensive and timely, Edible and Medicinal Mushrooms: Technology and Applications provides the most up to date information on the various edible mushrooms on the market. Compiling knowledge on their production, application and nutritional effects, chapters are dedicated to the cultivation of major species such as Agaricus bisporus, Pleurotus ostreatus, Agaricus subrufescens, Lentinula edodes, Ganoderma lucidum and others. With contributions from top researchers from around the world, topics covered include: Biodiversity and biotechnological applications Cultivation technologies Control of pests and diseases Current market overview Bioactive mechanisms of mushrooms Medicinal and nutritional properties Extensively illustrated with over 200 images, this is the perfect resource for researchers and professionals in the mushroom industry, food scientists and nutritionists, as well as academics and students of biology, agronomy, nutrition and medicine.